On Brands and Word of Mouth - Lovett, Mitchell J.; Peres, Renana; Shachar, Ron (Journal of Marketing Research, 2013)
Brands and word of mouth (WOM) are cornerstones of the marketing field, and yet their relationship has received relatively little attention. This study aims to enhance understanding of brand characteristics as antecedents of WOM by executing a comprehensive empirical analysis. For this purpose, the authors constructed a unique data set on online and offline WOM and characteristics for more than 600 of the most talked-about U.S. brands. To guide this empirical analysis, they present a theoretical framework arguing that consumers spread WOM on brands as a result of social, emotional, and functional drivers. Using these drivers, the authors identify a set of 13 brand characteristics that stimulate WOM, including three (level of differentiation, excitement, and complexity) that have not been studied to date as WOM antecedents. The authors find that whereas the social and functional drivers are the most important for online WOM, the emotional driver is the most important for offline WOM. These results provide an insightful perspective on WOM and have meaningful managerial implications for brand management and investment in WOM campaigns.